Neurochemical binding profiles of novel indole and benzofuran MDMA analogues. - Shimshoni,JA; Winkler,I; Golan,E; Nutt,D (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)
3,4-Methylenedioxy-N-methylamphetamine (MDMA) has been shown to be effective in the treatment of post-traumatic stress disorder (PTSD) in numerous clinical trials. In the present study, we have characterized the neurochemical binding profiles of three MDMA-benzofuran analogues (1-(benzofuran-5-yl)-propan-2-amine, 5-APB; 1-(benzofuran-6-yl)-N-methylpropan-2-amine, 6-MAPB; 1-(benzofuran-5-yl)-N-methylpropan-2-amine, 5-MAPB) and one MDMA-indole analogue (1-(1H-indol-5-yl)-2-methylamino-propan-1-ol, 5-IT). These compounds were screened as potential second-generation anti-PTSD drugs, against a battery of human and non-human receptors, transporters, and enzymes, and their potencies as 5-HT2 receptor agonist and monoamine uptake inhibitors determined. All MDMA analogues displayed high binding affinities for 5-HT2a,b,c and NEα2 receptors, as well as significant 5-HT, DA, and NE uptake inhibition. 5-APB revealed significant agonist activity at the 5-HT2a,b,c receptors, while 6-MAPB, 5-MAPB, and 5-IT exhibited significant agonist activity at the 5-HT2c receptor. There was a lack of correlation between the results of functional uptake and the monoamine transporter binding assay. MDMA analogues emerged as potent and selective monoamine oxidase A inhibitors. Based on 6-MAPB favorable pharmacological profile, it was further subjected to IC50 determination for monoamine transporters. Overall, all MDMA analogues displayed higher monoamine receptor/transporter binding affinities and agonist activity at the 5-HT2a,c receptors as compared to MDMA.